Effects of Plateau Pika Disturbance on the Spatial Heterogeneity of Vegetation in Alpine Meadows - Li, Jie; Qi, Hao Hao; Duan, Yuan Yuan; Guo, Zheng Gang (Frontiers in Plant Science, 2021)
Herbivory is one of the important factors that influence spatial heterogeneity of vegetation in grasslands. In this study, we focused on plateau pika (Ochotona curzoniae) to investigate the effects of the presence of small semi-fossorial herbivores and their disturbance intensity on the spatial heterogeneity of vegetation in alpine meadows across three sites in the Qinghai-Tibetan Plateau. A random stratified paired sampling method was used to collect vegetation data, and plant species richness at both fine and coarse scales were used to estimate the spatial heterogeneity of vegetation. This study showed that the presence of plateau pikas led to higher spatial heterogeneity of vegetation in alpine meadows, which increased linearly as the disturbance intensities of plateau pikas increased. The findings of this study demonstrate that small semi-fossorial herbivores have an important impact on the spatial heterogeneity of vegetation, and present a possible approach for estimating the effect of the presence of a small semi-fossorial herbivore and its disturbance intensity on the spatial heterogeneity of vegetation in grasslands.